The weaker sex in war : gender and nationalism in Civil War Virginia - Brill, Kristen, 1986- (Nation divided., 2022)
"Examining the relationship between middle- and planter-class white women who supported the Confederacy, this book demonstrates that elite and middle-class white Southern women--active at home and abroad--played an integral role in the construction of Confederate nationalism as both actors and symbols, and it traces the impact of and the memories surrounding these women's wartime activism into the twentieth century"--